Estudo da atividade anticâncer in vitro para complexos de Pd(II): avaliação dos substituintes dos ligantes tiossemicarbazonas - Lima, Mauro Almeida (Universidade Federal de São Carlos, 2023)
The group of cancer diseases has health global importance; therefore, research is developing out to improve existing therapies and new therapies. The drugs of Pt(II) bases are notably in cancer treatment and act on DNA structure. Other biological targets to cancer treatment are the topoisomerases enzymes, act in DNA replication and are overexpressed in tumors, and the cathepsin B enzyme, stimulate the cancer progression. Hence, the present work had proposed to study Pd(II) complexes as enzymatic inhibitors and to evaluate their anticancer potential through in vitro cell assays. Nine Pd(II) complexes were collected: 5 synthesized in this work and 4 by collaborators. All compounds are formed by triphenylphosphine and thiosemicarbazones, with generic structure [PdCl(PPh3)(TSC)]. The synthesized complexes were characterized by the techniques of NMR (1H, 13C and 31P), FTIR, UV-Vis, mass spectrometry and X-ray diffraction, since several single crystals were obtained. Cytotoxicity assays of the compounds were performed in cell lines: A2780, A2780cis, MDA-MB-231, MCF-7, SK-BR-3, MCF10-A, A549, MRC5 and A375 among which, the complexes of the B family were significantly more active in ovarian cells (IC50<1 µM) and breast cells (IC50~2 µM). A highlight of this assay was the complexes were more active than cisplatin and had high selectivity index (SI). In addition, the clonogenic survival, morphology, migration, and cell cycle assays were performed, through which two activity profiles were observed: cytotoxic and cytostatic. The Pd(II) complexes low interacted with DNA, were observed electrostatic interactions, and assay with HSA demonstrated an intermediate-static mechanism. Inhibition of TOPOIIα was observed only for the complexes PdA1, PdA2 and PdA3 which have a catalytic inhibitor profile, since they did not act on the beta isoform (TOPOIIβ). The PdC1 complex showed greater potential for CatB inhibition. Thus, the three families of complexes presented unique characteristics, and each one stood out in one part of the research, such as: catalytic inhibition of TOPOIIα (A), high cytotoxicity against breast and ovarian tumor lines (B), and ability to inhibit the enzyme CatB (C). Finally, it was demonstrated that Pd(II) complexes were presented as potential antineoplastic agents.
Study of in vitro anticancer activity for Pd(II) complexes: evaluation of substituents for thiosemicharbazone ligands
Keywords: Química Inorgânica; Câncer; Complexos metálicos; Paládio; Tiossemicarbazonas; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA::QUIMICA BIO-INORGANICA